Pengaruh Kualitas Produk Makanan dan Harga Terhadap Keputusan Pembelian Roti Gembong Gembul Pekanbaru - Almawaddah Almawaddah; Annisa Mardatillah (SYNERGY: Jurnal Bisnis dan Manajemen, 2026)
The purpose of this study is to analyze and explain the influence of Food Product Quality and Price on Purchasing Decisions at Roti Gembong Gembul Bukit Raya Pekanbaru. This study uses a quantitative method. The sampling method used is Purposive Sampling with a sample determination of 100 respondents. Data collection techniques used in this study are Questionnaires, interviews, observations, and documentation. The results of this study indicate that there is a significant and positive influence between food product quality and price on purchasing decisions. The conclusion is that food product quality and price have a positive and significant influence on purchasing decisions at Roti Gembong Gembul Bukit Raya Pekanbaru.